Efficacy of commercial and household denture cleansers against Candida albicans adherent to acrylic denture base resin: An in vitro study - M Nanditha Kumar; H M Thippeswamy; K N Raghavendra Swamy; Anil Kumar Gujjari (Wolters Kluwer Medknow Publications, 2012)
Aim: To evaluate and compare the efficacy of two commercial and two household denture cleansers against Candida albicans adherent to acrylic denture base resin. Materials and Methods: Fifty specimens of acrylic denture base resin (10 × 10 × 2 mm) were fabricated and processed according to the manufacturer's instructions. Sterile acrylic resin specimens were inoculated by immersing in Sabouraud broth containing C albicans for 16 hours at 37°C in an incubator. Then the specimens were washed and immersed in denture cleansers (four groups) - Clinsodent® (powder form), Fittydent® (tablet form), vinegar (4% acetic acid), diluted vinegar (50% diluted with water), and water (control group) for 8 hours at room temperature. After 8 hours the acrylic resin specimens were washed, fixed with methanol, and stained with crystal violet. Candida cells adherent to the acrylic resin specimens were counted under microscope. The number of cells adherent to the test samples were compared with that adherent to the control. Statistical Analysis: The data were analyzed using the independent-samples 't ' tests, analysis of variance (ANOVA), and Tukey's HSD test. Results: All the denture cleansers were highly effective against C albicans. The effectiveness of commercial denture cleansers was significant better than that of household denture cleansers. Fittydent® fared better than Clinsodent® , but the difference between the two was not statistically significant (P=.765). Vinegar was more effective than diluted vinegar (P<.05). Conclusion: Within the limitations of this in vitro study, denture cleansers were found to be effective in reducing C albicans cells adhering to dentures. The commercial denture cleansers (Fittydent® and Clinsodent® ) were more effective than household denture cleansers (vinegar and diluted vinegar).